Collective imagination and sociogenesis through the prism of imagining collective futures - (:unkn) unknown (My University, 2025)
The project will study the relationship between how people imagine the future and how social change transpires. We will explore the proposition that social change is guided by people’s imaginings of what the collective future could be like; by the visions of what is possible and anxieties about what should not happen. The aim is to construct a multi-level framework to account for the recursive relationship between social actuality and imagination of the collective futures that would explain the operations of imagination at the level of individuals, groups and society, as well as the interactions between them.
Keywords: Collective imagination; future; sociogenesis; utopia